Analisis Peremajaan Optimum Karet Rubber Optimal Replanting Analysis ( Studi Kasus di Kebun Musi Landas Sumatera Selatan) - Tirta Jaya Jenahar (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2003)
The case study on rubber replanting in Musi Landas, South Sumatra shows that both, Sutardi formula (1973) and Jenahar's (1986) provide the some economic live which is 25 years for the area of 2577 ha with replanted area of 103,08 ha per year. The result shows attaints that the net present value (NPV) is Rp.1.6 nillion per ha with the investment payback period of 17 years and the internal rate of return (IRR) 16.15 % per year.The method used in this research is optimum replanting analysis method. The analical method shows that the cash flow method developed by Jenahar (1986) is simpler than Sutardi's marginal method (1973) and gives similar result in term of the rubber tree's economic life. However, the cash flow formula could be used for feasibility assessment